HAK KESULUNGAN : Kajian Historis Kejadian 25:19-34 dan Maknanya bagi GMIM Jemaat Golgota Bukit Ranomuut - Lembong, Theresia Yashinta Tiara; Lumintang, Ferry S. (Educatio Christi, 2023)
The Birthright is a privilege for an firstborn. This birthright is a culture that has existed since the time of ancient Israel which is still often misinterpreted today. This right gives a mistaken view of the position of an firstborn. When in the story of Esau and Jacob who were brothers, loved by his father and mother, Esau looked down on the birthright and exchanged it for Jacob's red bean soup, so that Esau did not care about his privileges either by inheritance, for leadership or for the privileges he had as the firstborn and then he sold the birthright Jacob.